Diversity of stored-product beetles at the rice warehouses in Mataram City and Central Lombok Regency, Indonesia - Ayu Purnamasari; Hery Haryanto (Universitas Lancang Kuning, 2023)
Beetles, the order Coleoptera, are post-harvest rice product pests that cause severe quantitative and qualitative damage. Therefore, the diversity of pest beetles found in rice warehouses is essential because it leads to pest management by detecting and identifying beetles that can be the basis for making decisions in Integrated Pest Management (IPM). The study was conducted at two rice warehouses, Cakranegara I and Ubung, Indonesia, with rice sampling at five points diagonally on each side. Rice was taken using the Nobbe Trier tool inserted into the sack, and 100 g was taken as a rice sample. Rice sampling was conducted from June to July 2019, with five points diagonally on each side of a pile of rice. The results obtained four pest beetle species: Sitophilus oryzae, Cryptolestes ferrugineus, Oryzaephilus surinamensis, and Tribolium castaneum. Based on the Shannon Wiener index (H’) in Cakranegara I warehouse, the pest beetle found was only C. ferrugineus with a low diversity level of 1.60. Meanwhile, four pest beetle species were found in the Ubung warehouse S. oryzae, C. ferrugineus, O. surinamensis, and T. castaneum, with a moderate diversity level of 2.74. The differences in the diversity of pest beetles in storage were influenced by the rice warehouse's temperature and relative humidity (RH).